PEMBELAJARAN ETNOMATEMATIKA SEBAGAI KONSEP GEOMETRI PADA SITUS PARTITAAN NGAWONGGO - Erika Putri, Radita; Rochsun (Universitas Insan Budi Utomo, 2025)
Abstrak This study is designed to provide information that describes the geometric concepts found at the Partitaan Ngawonggo Site using a descriptive qualitative approach by collecting data such as analyzing, taking photos, and structured interviews. The steps are divided into three categories carried out in this study: data analysis, preparation, implementation, and introduction. The research subjects are the local community and the key to the Partitaan Ngawonggo Site. The report of the findings of this study found the existence of geometric concepts at the Partitaan Ngawonggo Site, such as the shape of a rectangular flat building at the Ngawonggo sacred bathing site, and the length of a square in the wall pattern bath. There are also buildings such as cylinders, rooms, and rectangular pyramids located in the area. It is possible to use the implications of geometric concepts at the Ngawonggo site as a substitute for traditional classroom mathematics instruction.